Increased prolidase activity and high blood monocyte counts in pediatric bipolar disorder. (January 2019) - Ceylan, Mehmet Fatih; Tural Hesapcioglu, Selma; Kasak, Meryem; Senat, Almila; Erel, Ozcan
Highlights: The prolidase activities were significantly higher in patients with PBD. The monocytes levels were significantly higher in patients with PBD. This increase in monocytes may play a role in the etiology of the disorder as an indicator of chronic inflammation. There is a clinical benefit from the early detection of PBD using serum prolidase activity levels and monocyte counts. Abstract: Various psychological, genetic, and biochemical factors are thought to be involved in the aetiology of pediatric bipolar disorder (PBD). However, few studies have evaluated the biochemical basis of PBD. The level of peripheral blood mononuclear cells and serum prolidase activity were determined in PBD and matched healthy comparison subjects. Blood from 38 (age range: 14–17) PBD-type I and 37 age- and gender-matched healthy comparison subjects was analyzed for numbers of neutrophils, lymphocytes, monocytes, lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR) and serum prolidase activity. The prolidase activity and monocyte count were significantly higher in PBD than the control group. There were no significant differences in numbers of neutrophils, lymphocytes, LMR and NLR between the patient and control groups. These results suggest that the immune system and prolidase activity may be activated in PBD. There is a clinical benefit from the early detection of PBD using serum prolidase activity levels and monocyte counts. Especially, prolidase activity may be a trait marker for diagnosing PBD. However, further studies are needed to verify these findings.